A Fuzzy Logic Based Proactive Maintenance scheduling on Communication Networks - Olajubu, E.A. (Ife Journal of Technology, 2013)
This paper presents a fuzzy logic methodology for scheduling predictive maintenance on communication networks. Lightweight agents were used to monitor and collect network elements status information at intervals of time which indicated the condition of each component, and the overall health of the network element. Data analyzer used to process status information of each component data was model with fuzzy logic Toolbox in MATLAB®. The results of the data analysis were used to determine the health condition of the network element. A prototype of the system was implemented in a simple case scenario but we expect the system to perform efficiently in a larger complex network. The result of the simple case scenario is presented.